Which strategies might improve local primary healthcare in Germany? An explorative study from a local government point of view - Bertolt Kuhn; Kim-Sarah Kleij; Sebastian Liersch; Jost Steinhäuser; Volker Amelung (BMC Family Practice, 2017)
Abstract Background Facing rising inequities and poorer accessibility of physicians in rural areas, new healthcare delivery structures are being considered to support local healthcare in German communities. To better understand perspectives on and attitudes towards different supplementary models, we examined attitudes among local politicians in the German federal state of Lower Saxony towards the suitability of supplementary care models. Methods As part of a cross-sectional study, we surveyed local politicians in Lower Saxony at the local authority and district levels (n = 449) by mail questionnaire. We asked for an assessment of four potential supplementary healthcare models at the local level: the use of trained medical assistants, patients’ buses, mobile physicians’ offices, and telemedicine. Results The response rate was 71.0% for mayors (n = 292) and 81.6% (n = 31) for county administrators. In summary, 72.4% of respondents supported the use of trained medical assistants, 48.9% voted for patients’ buses, 22.0% for mobile physicians’ offices, and 13.9% for telemedicine. Except for telemedicine, the politicians’ approval of the supplementary models in rural areas was higher than in urban areas. The assessment regarding the suitability of each model was not significantly connected with indicators of a positively or negatively assessed local healthcare situation. The analyses showed that the use of trained medical assistants was associated with the positive effects of division of labor and potential to relieve physicians. In contrast, there was skepticism about technical support via telemedicine, mostly due to concerns about its unsuitability for elderly people and the potential lower quality of healthcare delivery. Conclusion Local politicians widely accept the use of trained medical assistants, whereas the applicability of technical solutions such as telemedicine is perceived with skepticism. Therefore, the knowledge gap between evidence for and prejudices against telemedicine needs to be addressed more effectively. Reasons for the assessments of the presented models are more likely traceable to personal views than to assessments of the actual estimated local primary care situation.